Medical Writing and Research Methodology for the Orthopaedic Surgeon (Springer International Publishing, 2018)
This unique guide is designed to facilitate the complex task of getting a paper published in an orthopaedics journal. The editors have enlisted expert orthopaedic surgeons from prestigious academic institutions, who share essential advice on how to set up and write on your research. The book addresses fraud issues, the correct use of English and editing, how to develop a sound research methodology, and editors' and reviewers' expectations, along with the main reasons for rejection. The future of the Impact Factor, altmetrics and Open Access journals are also discussed, and will be of special interest to young faculty who are starting their research career. The chapters are structured in a reproducible and easy-to-follow format. In addition, the editors offer tips and tricks for non-native speakers writing in English. As such, the book provides an accessible and comprehensive resource for all those seeking guidance on how to publish their research work in the field of orthopaedics.